THE EFFECT OF MULTI LAYER SWITCHING FOR DATA TRANSFER SPEEDS ON COMPUTER NETWORK - Sudaryanto, Sudaryanto (Compiler, 2018)
The need for efficient, stable, fast and reliable network access is influenced by network quality, one of the factors influencing network quality is the management of network devices, while the network devices that are enforced are the Lancard, cable, Switch, Router, Wifi Access Point and Compuitary System . In this study researchers will focus on the influence of Multilayer Switch network devices for data transfer speeds on computer networks. Data transfer speed at layer 2 text data, image data,  video data faster 0,85 % than for speed tranfers on layer 3 text data, image data, video data.Keyword: Network, Switch Multilayer, Data Tranfer, Osi Layer